Validity and reliability of the Setswana translation of the Short Form-8 health-related quality of life health survey in adults - Sunday O. Onagbiye; Sarah J. Moss; Melainie Cameron (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2018)
Background: The absence of culturally relevant measures in indigenous languages could pose a challenge to epidemiological studies on health-related quality of life (HRQoL) in developing nations.